2014
DOI: 10.1007/978-1-4939-1462-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Computational Modeling of Vascular Morphogenesis Using Tissue Simulation Toolkit

Abstract: Computational modeling has become a widely used tool for unraveling the mechanisms of higher-level cooperative cell behavior during vascular morphogenesis. However, experimenting with published simulation models or adding new assumptions to those models can be daunting for novice and even for experienced computational scientists. Here, we present a step-by-step, practical tutorial for building cell-based simulations of vascular morphogenesis using the Tissue Simulation Toolkit (TST). The TST is a freely availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…We consider a population of cells on a grid that search for resources to be able to replicate. We explicitly account for cell shape and interactions by implementing a 2D hybrid Cellular Potts Model on a square lattice [3436]. Cells can adhere to each other if they express matching ligands and receptors on their surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider a population of cells on a grid that search for resources to be able to replicate. We explicitly account for cell shape and interactions by implementing a 2D hybrid Cellular Potts Model on a square lattice [3436]. Cells can adhere to each other if they express matching ligands and receptors on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…The model is a hybrid Cellular Potts Model implemented with the Tissue Simulation Toolkit [36]. A population of N cells exists on a regular square lattice Λ 1 ⊂ ℤ 2 .…”
Section: Modelmentioning
confidence: 99%
“…The authors showed that differences in the matrix binding affinity of vascular endothelial growth factor (VEGF) isoforms resulted in vastly different capillary morphologies. Merks and co-workers [94,95] …”
Section: Mathematical Models Of Vascularized Tumours and Angiogenesismentioning
confidence: 99%
“…It is the first work to study systemic modeling of tumor growth and immune response within an integrated 3D model (Figure 5). In addition, tumor progression is related to angiogenesis; therefore, it is necessary to integrate vascularization into ABM model to reflect the endothelial cells interaction with cancer cells through some key factors, such as VEGF [98]. Wang et al proposed an ABM model that integrates the angiogenesis into tumor growth to study the response of melanoma cancer under combined drug treatment [99].…”
Section: Several Classical Systemic Modeling Approachesmentioning
confidence: 99%